INTERPRETATION AND MODIFICATION OF FAIRY TALES IN - kizi, Israilova Sayera Tashpulat (International Journal of Psychosocial Rehabilitation, 2020)
In the article a fairy tale is considered as a prototext which serves as the base for secondary texts. Interpretation and modification as mechanisms of the creation of secondary texts are described.